2010
DOI: 10.4269/ajtmh.2010.10-0332
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Treatment Difficulties of Pyelonephritis in Pregnancy in Resource-Limited Settings

Abstract: Limited microbiology services impede adequate diagnosis and treatment of common infections such as pyelonephritis in resource-limited settings. Febrile pregnant women attending antenatal clinics at Shoklo Malaria Research Unit were offered urine dipstick, sediment microscopy, urine culture, and a 5-mL blood culture. The incidence of pyelonephritis was 11/1,000 deliveries (N = 53 in 4,819 pregnancies) between January 7, 2004 and May 17, 2006. Pyelonephritis accounted for 20.2% (41/203) of fever cases in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
(56 reference statements)
1
26
0
Order By: Relevance
“…America, 32 12 studies in Asia, [33][34][35][36][37][38][39][40][41][42][43][44] and 2 studies in Europe. 45,46 We contacted authors of 20 studies for more clarifications about their reports.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
See 1 more Smart Citation
“…America, 32 12 studies in Asia, [33][34][35][36][37][38][39][40][41][42][43][44] and 2 studies in Europe. 45,46 We contacted authors of 20 studies for more clarifications about their reports.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
“…For studies that lasted for more than 12 months, the midyear of the study period that actual sampling and laboratory evaluation was done was determined as the date of the study. Nine studies reported data on patients with symptomatic UTI, 24,27,29,[31][32][33]43,44,46 nine reported AB, 25,26,[34][35][36][37][40][41][42] and infection type in five studies 28,30,38,39,45 were indeterminate. Two studies included postpartum women.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
“…vivax infection [ 20 22 ]. Dengue, leptospirosis, typhoid fever and rickettsioses are common causes of fever in tropical areas [ 23 , 24 ] but whether the risk and severity of these diseases are higher in pregnancy is unclear [ 17 , 25 – 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of resistant organisms were cultured (20.9% of E. coli produced ESBL) although this is comparatively lower than the 37% reported from 97 samples (2009-2010) from two Thai hospital (Sirriraj Hospital in Bangkok and Songklanakarin Hospital, Songkhla, Southern Thailand) described in the Study for Monitoring Antimicrobial Resistance Trends (SMART) [34]. It is, however, five times higher than described in the same setting in adult febrile pregnant women just 8 years earlier (2004)(2005)(2006) [22]. In addition, rates of antibiotic resistance against cephalosporins, ampicillin, cotrimoxazole and gentamicin were comparable to E. coli susceptibilities of community-acquired infections in Asia [35].…”
Section: Discussionmentioning
confidence: 79%